Dynamic modelling and simulation of a multi-regime hybrid vehicle powertrain architecture. (22nd April 2008) - Wishart, Jeffrey; Zhou, Yuliang Leon; Dong, Zuomin; Firmani, Flavio
In this work, the dynamic model of a multi-regime hybrid vehicle powertrain architecture is presented. The study focuses on the formulae governing the operation of the planetary gear systems in the powertrain and on the performance of a more complex heavy-duty vehicle with varying loading conditions. The model is compared with models of the Toyota Hybrid System, a generic full-parallel design, and a conventional powertrain, all implemented for a commercial delivery vehicle in the ADVISOR simulation software. Computer simulations in ADVISOR compare the performance of the various designs, using fuel consumption as the performance metric, for four different drive cycles common for this vehicular application. The results demonstrate that the multi regime architecture provides significantly improved performance to that of the conventional and THS design and comparable performance to that of the full parallel hybrid design. The study confirms that the multi-regime architecture presents unique advantages for wide-ranging road loads and vehicle payloads and that multi-regime designs likely represent the future of hybrid vehicle technology.